CORPORATE: THE TEACHING PRACTICE OF THE PHYSICAL EDUCATION TEACHER (Fiep Bulletin - online, 2020)
Based on pedagogical practices, the Corporeity process becomes necessary for the child's cognitive and motor development. For this, the educational praxis centered on the teaching action of the Physical Education professional becomes paramount. In this sense, the Corporeality theme will be developed in praxis within Physical Education classes, aiming to analyze the contributions that the Corporeality can offer to the kindergarten students.This research focuses on the principles of qualitative nature, held in a School of the Municipal Education Network, located in the city of Ponta Grossa - Pr. This work consists of approaching this theme with activities such as: conversation circles with students, body part posters, video presentations and hands-on classes.Thus, the teacher will have a very important role throughout their classes, helping them to know and identify their body, so that from this first phase they understand the importance of Corporeality with integration and socialization activities.As a result of this research, it was emphasized that Corporeality has been contributing to the motor development and recognition of the body by children.Thus, Physical Education aims to increase, in the face of activities on Corporeality, performing body movements for the development and learning about body culture.